Perancangan Sistem Informasi Pencarian Jasa Pembersihan Rumah Berbasis Website - Novarezi, Wendi Tri; Rahim, Robbi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Technology makes many people live a fast-paced and instant life so they need other help to take care of household needs such as house cleaning help, many difficulties in finding help with house cleaning services arise from the distrust of a service provider towards house cleaning workers so they are very good If a website is created to search for house cleaning services, the website can be held responsible starting from security, price transparency and the quality that can be provided. The existence of a website for searching for house cleaning services helps people who need house cleaning assistance to more easily consult about the condition of their house and the price they are looking for according to their budget without needing to make an order directly by visiting the place or company, just using a cell phone, everything is more convenient. The design of this website has 3 user views, namely administration, workers/service bidders and customers or service users. The design uses the HyperTex Markup Language and Cascading Style Sheet programming language. The results of this research produce a website with user-friendly features.